The impact of acquiring unrestricted work authorization on Romanian and Bulgarian migrants in the United Kingdom - Ruhs, M; Wadsworth, J (SAGE Publications, 2017)
When Romania and Bulgaria (the so-called A2 countries) joined the European Union in 2007, the United Kingdom imposed temporary restrictions on the employment and welfare entitlements of A2 citizens that lasted until January 1, 2014. This article analyzes the impact of the removal of these restrictions on the labor market outcomes and use of welfare benefits of A2 migrants. Applying difference-in-difference analysis to data from the UK’s Labour Force Survey, the results suggest that acquiring unrestricted work authorization had a significant negative impact on the incidence of self-employment among A2 migrants but there are no discernible effects on other labor market outcomes or on their receipt of a range of welfare benefits. The article offers potential explanations for these results.